2011
DOI: 10.1186/1478-4505-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Access to Subsidized Artemisinin-based Combination Therapy through Accredited Drug Dispensing Outlets in Tanzania

Abstract: BackgroundIn Tanzania, many people seek malaria treatment from retail drug sellers. The National Malaria Control Program identified the accredited drug dispensing outlet (ADDO) program as a private sector mechanism to supplement the distribution of subsidized artemisinin-based combination therapies (ACTs) from public facilities and increase access to the first-line antimalarial in rural and underserved areas. The ADDO program strengthens private sector pharmaceutical services by improving regulatory and superv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 10 publications
1
68
1
Order By: Relevance
“…Detectable residual antimalarial levels in recruited participants were unexpectedly high. This might be explained by uncontrolled prescription of AL, a first-line malaria treatment, which is highly available and easily accessible from both private and public facilities (42,43). The prevalence of residual antimalarial among participants was higher than what was found 5 years ago from in vivo studies in Ifakara (Tanzania) and Praeh Vihear (Cambodia), which reported 74.3% and 50%, respectively (28,29).…”
Section: Discussioncontrasting
confidence: 44%
“…Detectable residual antimalarial levels in recruited participants were unexpectedly high. This might be explained by uncontrolled prescription of AL, a first-line malaria treatment, which is highly available and easily accessible from both private and public facilities (42,43). The prevalence of residual antimalarial among participants was higher than what was found 5 years ago from in vivo studies in Ifakara (Tanzania) and Praeh Vihear (Cambodia), which reported 74.3% and 50%, respectively (28,29).…”
Section: Discussioncontrasting
confidence: 44%
“…For those who did go to a health facility for an acute illness, most ended up taking their prescriptions to ADDOs to fill, suggesting that the facility was out-of-stock. This aligns with other data on the percentage of ADDO sales that are based on prescriptions [11]. …”
Section: Discussionsupporting
confidence: 90%
“…The dispensers also fill prescriptions that customers bring in from the public/nongovernmental organization (NGO) health facility. Because they function as part of the health system, ADDOs have been used as a platform for public health interventions, including increasing access to artemisinin-based combination therapy for malaria, and they have been incorporated into multiple public health strategies, from family planning to achievement of the Millennium Development Goals [11–13]. …”
Section: Introductionmentioning
confidence: 99%
“…Increasing availability and accessibility of ACTs will limit the usage of non-ACTs such as chloroquine. A Tanzanian study showed that anti-malaria monotherapy was being crowded out of the market [14]. In the current study, chloroquine is available in 80% of the studied pharmacies and was the most common drug purchased for malaria treatment in the pre-intervention period.…”
Section: Discussionmentioning
confidence: 66%
“…Interventions to increase accessibility of ACTs in private pharmacies were supported by a subsidized artemisinin-based combination therapy approach in different developing countries, resulting in an increase in marketing and an increase in malaria patients being treated with ACTs [14,15]. In this pilot project, despite the marketing of ACTs and other recommended antimalaria drugs, the private sector did not support any marketing interventions applied to increase the availability or use of ACTs in the private sector.…”
Section: Discussionmentioning
confidence: 97%